2012
DOI: 10.1111/j.1749-6632.2012.06576.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of N‐cadherin in the regulation of hematopoietic stem cells in the bone marrow niche

Abstract: Cell-cell and cell-extracellular matrix interactions between hematopoietic stem cells (HSCs) and their niches are critical for the maintenance of stem cell properties. Here, it is demonstrated that a cell adhesion molecule, N-cadherin, is expressed in hematopoietic stem/progenitor cells (HSPCs) and plays a critical role in the regulation of HSPC engraftment. Furthermore, overexpression of N-cadherin in HSCs promoted quiescence and preserved HSC activity during serial bone marrow (BM) transplantation (BMT). Inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 33 publications
0
36
0
2
Order By: Relevance
“…The marrow is located within the bone, in which osteoblasts form a well-defined lining to which quiescent HSCs adhere (238,311,312). The association between these two cell types makes the distribution of osteoblasts a valid reference point for the recognition of HSC niches (18). Additionally, the possibility to ablate the niches and create empty structures that can be repopulated has provided the bases for prospective studies of HSCs.…”
Section: Cpc Nichesmentioning
confidence: 99%
“…The marrow is located within the bone, in which osteoblasts form a well-defined lining to which quiescent HSCs adhere (238,311,312). The association between these two cell types makes the distribution of osteoblasts a valid reference point for the recognition of HSC niches (18). Additionally, the possibility to ablate the niches and create empty structures that can be repopulated has provided the bases for prospective studies of HSCs.…”
Section: Cpc Nichesmentioning
confidence: 99%
“…Therefore, the potential for new insights into the mobility of fetal liver can be achieved through monitoring the expression of N-cadherin. [23,24] Figure 1. An unfolded protein response produces protein kinase RNA-like endoplasmic reticulum kinase (PERK) stress, and the resultant oxidative stress will result in reactive oxygen species (ROS) induced damage.…”
Section: N-cadherinmentioning
confidence: 98%
“…64,65 Further work has indicated that key events may occur around sinusoidal perivascular niche that may involve endothelial cells, pericytes, CXCL abundant reticular cells, sinusoidal-megakaryocyte cells, neural crest cells, osteoblasts, osteoclasts, T cells, mesenchymal stem cells, macrophages, non-myelinating Schwann cells and preadipocytic fibroblasts. 6672 A large number of putative regulators of the niche have also been described, including CXCL12, 73 E-selectin, 74 VEGFR 2, 75 N-cadherin 76 and osteopontin 77 and membrane bound steel factor. 78 Although these entities have various effects on hematopoietic stem cells their true role as niche maintenance factors is uncertain, except for that of membrane bound SCF.…”
Section: A Consideration Of Him or Nichesmentioning
confidence: 99%